Miíase humana por Dermatobia hominis (Linneaus Jr.) (Diptera, Cuterebridae) e Cochliomyia hominivorax (Coquerel) (Diptera, Calliphoridae) em Sucessão Parasitária - Batista-da-Silva, José Antonio (2009)
O objetivo deste trabalho foi relatar um caso raro de sucessão parasitária de duas espécies de larvas de moscas produtora de miíase primária, Dermatobia hominis e Cochliomyia hominivorax, em um jovem de 12 anos atendido em um hospital público no município de São Gonçalo (RJ). Human Myiases for Dermatobia hominis (Linnaeus Jr.) (Diptera, Cuterebridae) and Cochliomyia hominivorax (Coquerel) (Diptera, Calliphoridae) in Parasitic Succession Abstract. The objective this work was to tell a rare case of parasitic succession of two species of larvae of flies producing of primary myiases, Dermatobia hominis and Cochliomyia hominivorax, in a 12 year-old youth assisted in an public hospital in São Gonçalo (RJ).